Pengembangan media komik dengan metode picture and picture untuk meningkatkan keterampilan literasi matematika kelas IV - Rakasiwi, Nilam (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2019)
AbstractIn Indonesia, mathematical literacy in International scope is still not satisfying. In order to increase mathematical literacy ability, it can be done by applying some variation of learning methods supported by the utilization of learning media. The goal of this study is to develop and examine the validity, the practicality, and the effectiveness of comic media by picture and picture method to increase mathematical literacy ability of grade 6th students. This RD study used the ADDIE development model combined with steps in making comics by Sadiman. Those steps were analysis (analyzing the needs, goal and main material), design (synopsis, first step), development (prototype product, evaluation, revision, and last script), implementation (trials), and evaluation (final product). The validity of the product could be seen from expert judgment by using material, media, and learning expert validation instrument. The practicality of the product was done by the students’ response questionnaire instrument to the media. The effectiveness of the product was seen from one class trial by one group pre-test post-test, and the result was processed using Paired-Samples T-Test check with the help of SPSS 20.0. The result of this study was the comics media to increase grade 6th students’ mathematical literacy ability. Comics media proved to be valid from material and media aspects. Comics media proved to be practice from students’ response questionnaire. Comics media also proved to be effective based on the result of the pre-test, post-test and Paired-Samples T-Test check.Keywords: Comics, Mathematical Literacy, Picture and Picture